Hemodynamic features of athletes` physical working capacity in view of autonomic regulation type - Sherstyuk, S. A.; Kapilevich, L. V.; Sherstyuk, A. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify hemodynamic features of the physical working capacity of highly-skilled athletes under aerobic and anaerobic physical loads taking into account the type of autonomic regulation.